The role of faith-based organisations in the care of people living with HIV/AIDS in Swaziland - Clarkson, Stephanie E. (University of Manchester, 2014)
The scale and effect of the HIV/AIDS pandemic in countries such as Swaziland has emphasised the need for multisectoral collaborations. Multisectoral collaborations can utilise the strengths of different organisations in order to effectively respond to the pandemic, thereby preventing further declines in life expectancy and living standards. Hence, in contexts such as Swaziland, civil society organisations have a valuable role to play in the delivery of HIV/AIDS related prevention, care and treatment services. This includes faith-based organisations which are recognised in literature as providing a significant proportion of health related services in developing countries, particularly in sub-Saharan Africa. However, the relationship between faith and development and the role of faith-based organisations in development has been debated in the literature. Some donors and development agencies have been cautious of engaging with faith-based organisations due to fear of them proselytising or exacerbating HIV/AIDS related stigma and discrimination. However, others hold faith-based organisations to be distinctive and have a comparative advantage over secular organisations in the delivery of development related services. One reason given for their distinctiveness is the assumption that they provide a holistic approach to the care of people living with HIV/AIDS, meeting their various physical, psychological, social and spiritual needs. This dissertation explores the ways in which faith-based organisations, in comparison to secular non-governmental organisations, meet the physical, psychological, social and spiritual needs of people living with HIV/AIDS. It will apply a needs-based quality of life framework in order to evaluate the impact that the activities of the participating organisations have on the health related quality of life of people living with HIV/AIDS. This is of importance since the provision of care and treatment for people living with HIV/AIDS not only aims to increase their life expectancy, but also their quality of life. The dissertation will specifically make reference to two case studies: Shiselweni Home-Based Care and The AIDS Information and Support Centre. Using findings from literature, secondary data and primary research conducted in the form of a qualitative questionnaire, the dissertation seeks to answer the primary research question: Are the services faith-based organisations provide for people living with HIV/AIDS more holistic in their nature than those of secular nongovernmental organisations? The research found that the services both Shiselweni Home-Based Care and The AIDS Information and Support Centre provide for people living with HIV/AIDS are holistic in nature, meeting physical, psychological, social and spiritual needs. However, faith-based organisations may better be able to provide spiritual care to people living with HIV/AIDS due to their ideology and ethos.
Free